Comparability of Interviewer-Administration Versus Self-Administration of the Functional Assessment of Chronic Illness Therapy-Tuberculosis (FACIT-TB) Health-Related Quality of Life Questionnaire in Pulmonary Tuberculosis Patients. Issue 1 (June 2016) - Dujaili, Juman; Sulaiman, Syed; Awaisu, Ahmed; Hassali, Mohamed; Blebil, Ali; Bredle, Jason
Abstract Objective To investigate the extent to which two different modes of administration (interview by a trained interviewer versus self-administration) yielded a comparable estimate of health-related quality of life (HRQL) in patients with pulmonary tuberculosis (PTB). Methods The study was conducted between September 2012 and July 2013, among consecutive patients treated for PTB at the Thoracic and Respiratory Disease Specialist Centre in Baghdad, Iraq. The mode of administration of the functional assessment of chronic illness therapy-tuberculosis (FACIT-TB), a new TB-specific HRQL instrument, was recorded at baseline in 305 subjects. Results Although the FACIT-TB questionnaire was designed for self-administration, most patients in our sample (n  = 193, 63.3 %) requested some help from an interviewer to fill out the questionnaire. Patients capable of self-administration were younger (38.2 ± 12.9 years vs. 43.6 ± 16.4 years, p  = 0.005) and required less time to complete the questionnaire (14.6 ± 3.2 min vs. 17.2 ± 2.6 min, p  < 0.001) compared to those who were interviewed by a trained interviewer. No differences in gender were observed between the two groups. HRQL scores across all domains for those who were interviewed were slightly lower than those who answered the questionnaire by self-administration. However, the results did not reach statistical significance (p  > 0.05). Conclusions The study demonstrates that the administration of FACIT-TB instrument using either self-administration or interviewing techniques has resulted in a comparable estimate of HRQL among patients with PTB. The FACIT-TB instrument is able to accommodate the needs of patients with diverse social, educational, and functional skills.